2019
DOI: 10.1088/1674-1137/43/6/064106
|View full text |Cite
|
Sign up to set email alerts
|

High-K isomer and the rotational properties in the odd-Z neutron-rich nucleus M163Eu *

Abstract: The newly observed isomer and ground-state band in the odd-Z neutron-rich rare-earth nucleus 163 Eu are investigated by using the cranked shell model (CSM) with pairing treated by the particlenumber conserving (PNC) method. This is the first time detailed theoretical investigations are performed of the observed 964(1) keV isomer and ground-state rotational band in 163 Eu. The experimental data are reproduced very well by the theoretical results. The configuration of the 964(1) keV isomer is assigned as the thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…As it was known, the virtual electron (VE) progresses of occupied and unoccupied states were the main contribution to the overall SHG effect. [ 44 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was known, the virtual electron (VE) progresses of occupied and unoccupied states were the main contribution to the overall SHG effect. [ 44 ]…”
Section: Methodsmentioning
confidence: 99%
“…As it was known, the virtual electron (VE) progresses of occupied and unoccupied states were the main contribution to the overall SHG effect. [44] CCDC: 2194173-2194175 contain the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/ data_request/cif.…”
Section: Crystal Structure Determinationmentioning
confidence: 99%
“…The gliding arc is in the B-G mode, and the voltage and current waveforms are shown in figure 12(b). From the voltage and current waveforms, it is found that the characteristics of the B-G mode are the alternating positive and negative breakdowns caused by the periodic phase change of the AC power supply [42]. At the moment of breakdown, the current has an ampere-level pulse peak, which can reach a maximum of 7.5 A.…”
Section: Breakdown Gliding Mode (B-g)mentioning
confidence: 99%
“…In 1991, Patyk and Sobiczewski investigated the ground state properties of the heaviest even-even nuclei with proton numbers -114 and neutron numbers -168 using the MMM and found that the degree of freedom is important for binding energies and the formation of deformed shells [23,28]. Additionally, has a considerable influence on the moments of inertia [29,30] and high-K isomers [31,32]. The microscopic description of the structure of SHN can be achieved using density functional theories, with few studies investigating the influence of on the binding energy and shell structure of SHN to date.…”
Section: Introductionmentioning
confidence: 99%